An Introduction to clinical laboratory science - Clerc, Jeanne M (Mosby, 1992)
Eastern Michigan University, Ypsilanti. Introductory text for college students to clinical laboratory science, formerly called medical technology. Deals primarily with the social and professional aspects of CLS such as personality, certification, career opportunities, ethics. 3 U.S. contributors.
Keywords: volba povolání; chemie, klinická chemie; Clinical Laboratory Techniques; klinické laboratorní techniky; technologie lékařská; Career Choice; Medical Laboratory Science